Performance enhancement of a biofilter with pH buffering and filter bed supporting material in removal of chlorobenzene. (July 2020) - Han, Meng-Fei; Wang, Can; Yang, Nan-Yang; Hu, Xu-Rui; Wang, Yong-Chao; Duan, Er-Hong; Ren, Hong-Wei; Hsi, Hsing-Cheng; Deng, Ji-Guang
Abstract: Acidic substances, which produced during chlorinated volatile organic compounds, will corrode the commonly used packing materials, and then affect the removal performance of biofiltration. In this study, three biofilters with different filter bed structure were established to treat gaseous chlorobenzene. CaCO3 and 3D matrix material was added in filter bed as pH buffering material and filter bed supporting material, respectively. A comprehensive investigation of removal performance, biomass accumulation, microbial community, filter bed height, voidage, pressure drops, and specific surface area of the three biofilters was compared. The biofilter with CaCO3 and 3D matrix material addition presented stable removal performance and microbial community, and greater biomass density (209.9 kg biomass/m 3 filter bed) and growth rate (0.033 d −1 ) were obtained by using logistic equation. After 200 days operation, the height, voidage, pressure drop, specific surface area of the filter bed consisted of perlite was 27.4 cm, 0.39, 32.8 Pa/m, 974, 89 m 2 /m 3, while those of the filter bed with CaCO3 addition was 28.2 cm, 0.43, 21.3 Pa/m, and 1021.03 m 2 /m 3, and those of the filter bed with CaCO3 and 3D matrix material addition was 28.7 cm, 0.55, 17.4 Pa/m, and 1041.60 m 2 /m 3 . All the results verified the biofilter with CaCO3 and 3D matrix material addition is capable of sustaining the long-term performance of biofilters. CaCO3 could limit the changes of removal efficiency, microbial community and filter bed structure by buffering the pH variation. And 3D matrix material could maintain the filter bed structure by supporting the filter bed, regardless of the buffering effect. Graphical abstract: Image 1 Highlights: Acidic products affected the removal performance and filter bed structure. CaCO3 could buffer the pH variation and maintain stable removal performance. 3D matrix material could support the filter bed when CaCO3 was consumed. CaCO3 and 3D matrix material could enhance the filter bed structure proprieties. The performance with CaCO3 and 3D matrix material was stable and efficient.